2016
DOI: 10.12973/edupij.2016.53.5
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships between Occupational Professionalism and Organizational Cynicism of Teachers

Abstract: The purpose of this study is to explore the relationships between occupational professionalism and organizational cynicism levels of teachers. The sample of this study, designed as a survey research, consists of 436 teachers employed in schools in the city center of the province of Denizli, Turkey. The data of the study were collected through the administration of Teachers' Occupational Professionalism Scale and Organizational Cynicism Scale to the sample group. In data analysis, descriptive statistics, t-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
5
0
6
Order By: Relevance
“…These findings concur with the findings reported in the literature on occupational professionalism (Altinkurt & Ekinci, 2016;Altinkurt, & Yilmaz, 2014;Çelik & Yılmaz, 2015;Yorulmaz et al, 2015). In light of these findings, it can be argued that teachers do not invest enough efforts to acquire up-to-date knowledge and skills required by their profession and their contribution to their organizations is relatively limited.…”
Section: Discussionsupporting
confidence: 91%
“…These findings concur with the findings reported in the literature on occupational professionalism (Altinkurt & Ekinci, 2016;Altinkurt, & Yilmaz, 2014;Çelik & Yılmaz, 2015;Yorulmaz et al, 2015). In light of these findings, it can be argued that teachers do not invest enough efforts to acquire up-to-date knowledge and skills required by their profession and their contribution to their organizations is relatively limited.…”
Section: Discussionsupporting
confidence: 91%
“…Teachers who took part in the research stated that they exhibited the least professionalism in personal development. The order that this study presents for the sub-aspects of professionalism is consistent with the results of Altinkurt and Ekinci (2016), Altınkurt and Yılmaz (2014), Çelik and Yılmaz (2015), and Yorulmaz et al (2015).…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 90%
“…Based on the participants' opinions, it is possible to say that female teachers put out more occupational sensitivity and emotional labor compared to their male counterparts. Altinkurt and Ekinci (2016), Çelik and Yılmaz (2015) and Yorulmaz et al (2015) also concluded in their research that there is a significant difference according to gender in the same aspects, in favor of females. Altınkurt and Yılmaz (2014) only identified a significant difference by gender in contribution to the institution, favoring males.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Ekiz'e (2003) göre, bireysel olarak öğretmenlerin öğretmenlik rolünü oynayabilmesi ve kültürel olarak öğrencilerin toplumsal ihtiyaçlara göre yetiştirilebilmesi için yeterli bilgi ve beceriye sahip olmaları gerekmektedir. Bazı araştırma bulgularına (Altınkurt ve Ekinci, 2016;Karaca, 2015) Tablo.1'de yer alan, öğretmenlik mesleği genel yeterlikleri, öğretmenlerin kendi yetkinlik düzeylerini ve geliştirilmesi gereken yönlerini belirlemelerinde, öğretmen adayı yetiştiren yükseköğretim kurumlarının öğretim programlarının düzenlenmesinde, öğretmenlerin mesleğe kabul ve adaylık süreçlerinde, meslekî gelişim ihtiyaçlarının tespit edilmesinde ve bu ihtiyaçları gidermeye yönelik faaliyetlerin planlanmasında, öğretmenlerin performanslarının değerlendirilmesinde, kariyerlerini geliştirmelerinde ve öğretmenlik mesleğinin statüsünün güçlendirilmesi çalışmalarında dikkate alınacak temel bir referans metin olma özelliği taşımaktadır (MEB, 2017:9). Ayrıca, yeterliklerin öğretmen yetiştirme ve geliştirme sürecinde temel bir kaynak olarak YÖK, sivil toplum örgütleri, sendikalar ile kamu kurum ve kuruluşları tarafından belirlenecek politika ve uygulamalarda eşgüdüm sağlayabileceği belirtilmektedir.…”
Section: öğRetmenlikte Meslekî Gelişimunclassified